2018
DOI: 10.1101/387407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pivotal role of serine 225 phosphorylation in the function of hepatitis C virus NS5A revealed with the application of a phosphopeptide antiserum and super-resolution microscopy

Abstract: 241, importance: 150, main text (excluding figure legends): 4984 Abstract 18NS5A is a multi-functional phosphoprotein that plays a key role in both viral replication 19 and assembly. The identity of the kinases that phosphorylate NS5A, and the 20 consequences for HCV biology, remain largely undefined. We previously identified 21 serine 225 (S225) within low complexity sequence (LCS) I as a major phosphorylation 22 site and used a phosphoablatant mutant (S225A) to define a role for S225 23 phosphorylation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…In line with the present data, previous studies showed alanine mutations in serine 225 led to NS5A hyper-phosphorylation reduction and replication of HCV genotype 2 [4,58,59]. In addition, Goonawardane et al [60] focused on serine 225 (S225) and determined the contribution of S225 phosphorylation in the regulation of genome replication, interactions of NS5A with several host proteins, and the sub-cellular localization of NS5A. Mutations can affect the phosphorylation sites and our data suggested mutation in amino acid 131 could omit this phosphorylation site in 1a genotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the present data, previous studies showed alanine mutations in serine 225 led to NS5A hyper-phosphorylation reduction and replication of HCV genotype 2 [4,58,59]. In addition, Goonawardane et al [60] focused on serine 225 (S225) and determined the contribution of S225 phosphorylation in the regulation of genome replication, interactions of NS5A with several host proteins, and the sub-cellular localization of NS5A. Mutations can affect the phosphorylation sites and our data suggested mutation in amino acid 131 could omit this phosphorylation site in 1a genotype.…”
Section: Discussionsupporting
confidence: 92%
“…There is some evidence showed NS5A induces liver pathogenesis, steatosis, and hepatocellular carcinoma that NS5A phosphorylation can affect these important functions directly or indirectly [62]. Furthermore, there are some reports suggested S225 phosphorylation disruption reduced the HCV replication [60] and virus assembly [16,47,59]. NS5A is a target for DAAs such as daclatasvir (DCV) that S225 can be one of the targets for such effective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, hierarchical phosphorylation has been described for β-catenin, in which Ser45 phosphorylated by CK1α primes it for hyperphosphorylation by glycogen synthase kinase 3 (GSK-3) (38, 39), which triggers its ubiquitination and proteasomal degradation (40). A similar phosphorylation mechanism has recently been described for nonstructural protein NS5A of the hepatitis C virus (HCV), with the hyperphosphorylation cascade primed by the initial phosphorylation of serine 225 by CK1α and the subsequent phosphorylation of neighboring residues involving other kinases (41, 42). Moreover, NS5A phosphorylation has been shown to play a key role in controlling the establishment of replication complexes during HCV infection (43).…”
Section: Discussionmentioning
confidence: 64%
“…Proteins were separated by electrophoresis on a 7.5 % SDS-PAGE gel, and following electrophoresis, proteins were transferred onto PVDF membrane and blocked with 50 % (v/v) Odyssey blocking buffer (LiCor) in Tris-buffered saline (TBS). The membrane was then incubated with primary antibody as labelled, sheep anti-NS5A [15], rabbit anti-pS225 [16] or rabbit anti-pS232 [17] at 4 °C overnight. After washing with TBS, membranes were incubated with fluorescently labelled anti-sheep (800 nm) and anti-rabbit (680 nm) secondary antibodies for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, DBN3a NS5A did exhibit the expected two bands corresponding to basally and hyper-phosphorylated species, however, compared to JFH-1, the ratio of hyper : basally phosphorylated species was much lower. To investigate this further, we used antisera specific for NS5A phosphorylated at either S225 [16] or S232 [17]. These antisera had been shown to detect hyper-phosphorylated NS5A only, consistent with hierarchical phosphorylation of serine residues within LCSI.…”
Section: Evaluation Of Ns5a Expression and Phosphorylationmentioning
confidence: 99%